1998
DOI: 10.1006/viro.1997.8998
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Rat Bone Marrow Cells by Friend Murine Leukemia Virus Envelope Proteins

Abstract: In a retroviral rat model, we have investigated the nontransforming effects of murine leukemia virus FB29 on the bone marrow. Upon intraperitoneal inoculation with murine leukemia virus FB29 of either neonatal or adult rats, bone marrow cells became massively infected within the first 12 days postinoculation. In neonatally inoculated rats, a persistent productive bone marrow infection was established, whereas in rats inoculated as adults, no infected bone marrow cells could be detected beyond 12 days postinocu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2000
2000
2003
2003

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…However, it is unlikely, because FB29 virus, which does not contain the FVb1 motif ( Fig. 4), has very low or no leukemogenicity in rats (17). Therefore, we were able to demonstrate that the contribution of the enhancer region, and in particular the FVa motifs, is important in the induction of thymoma in rats.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…However, it is unlikely, because FB29 virus, which does not contain the FVb1 motif ( Fig. 4), has very low or no leukemogenicity in rats (17). Therefore, we were able to demonstrate that the contribution of the enhancer region, and in particular the FVa motifs, is important in the induction of thymoma in rats.…”
Section: Discussionmentioning
confidence: 71%
“…It has been reported that PVC211, FB29 and NT40 do not induce leukemia in rats, as they do in mice (16,17,23,25). However, clone A8 has high leukemogenic potential against both mice and rats (25).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Purification, subsequent immunostaining, immunoblotting, and cytofluorometric analyses of microglia and of peritoneal macrophages were performed as described in detail before (5,14,25). Briefly, brains were removed from perfused animals, stripped of meninges, enzymatically digested, and subjected to density gradient centrifugation.…”
Section: Methodsmentioning
confidence: 99%
“…mRNA was isolated from cells and tissues, employing oligo(dT) 25 Dynabeads following the recommendations of the manufacturer (Dynal). After Northern blotting, blots were probed with a viral envelope-specific 32 P-labeled probe (14) as well as with a 32 P-labeled probe for a housekeeping gene, rat glyceraldehyde-3-phosphate dehydrogenase.…”
Section: Methodsmentioning
confidence: 99%